Operation Control Method for Degraded Trains after Shanghai Rail Transit Lines 3 and 4 Signaling System Upgrade and Renovation - LI Yongzheng (Chengshi guidao jiaotong yanjiu)
Objective After the upgrade of Shanghai Rail Transit Lines 3 and 4 signaling systems, their functions are highly concentrated in the on-board train controller. In the event of on-board train controller failure leading to train degraded status, the operational capacity of the line will decrease significantly, requiring a safe and efficient withdrawal of degraded trains from service. Method The structural characteristics of TACS （train autonomous circumambulate system） equipment for Shanghai Rail Transit Lines 3 and 4 are presented, the operational scenarios for train degradation are analyzed, and the operation control methods applicable after train degradation based on equipment role are elaborated. Result & Conclusion After a train enters the degraded state, the wayside train controller will take over the resource management from trackside resource controller. Based on the operational tasks assigned by train scheduling, a back-up localization system is utilized to replace the on-board train manager for resource interaction with the trackside resource managers and other trains，with signal lights serving to direct train operation. This method maintains the tracking logic for train-to-train communication, and is suitable for line upgrades by avoiding to add equipment on trackside and reducing construction and maintenance costs.